A "Triple A" Typology of Responding to Negative Consumer-Generated Online Reviews. (August 2017) - Sparks, Beverley A.; Bradley, Graham L.
Increasingly, consumers are posting online reviews about hotels, restaurants, and other tourism and hospitality providers. While some managers are responding to these reviews, little is known about how to respond and how to do so effectively. Drawing on the service recovery, justice, and electronic word-of-mouth literatures, we developed a typology of management responses to negative online reviews of hotel accommodation. An initial version of the typology was verified through interviews with eight industry experts. The final "Triple A" typology comprised 19 specific forms of managerial responses subsumed within the three higher-level categories of acknowledgements, accounts, and actions. The typology was tested on a sample of 150 conversations drawn from the website, TripAdvisor. Most responses included an acknowledgement of the dissatisfying event, an account (explanation) for its occurrence, and a reference to action taken. Responses differed between top- and bottom-ranked hotels. Propositions for extending this area of research are provided.